2017
DOI: 10.3389/fpls.2017.01339
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Lipidomics and Proteomics of Lipid Droplets in the Mesocarp and Seed Tissues of Chinese Tallow (Triadica sebifera)

Abstract: Lipid droplets (LDs) are composed of a monolayer of phospholipids (PLs), surrounding a core of non-polar lipids that consist mostly of triacylglycerols (TAGs) and to a lesser extent diacylglycerols. In this study, lipidome analysis illustrated striking differences in non-polar lipids and PL species between LDs derived from Triadica sebifera seed kernels and mesocarp. In mesocarp LDs, the most abundant species of TAG contained one C18:1 and two C16:0 and fatty acids, while TAGs containing three C18 fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 85 publications
1
32
0
Order By: Relevance
“…Therefore, the first goal in this study was to investigate the proteome of LDs to extend the number of known LD-bound proteins. Tobacco pollen tubes were chosen, as LDs of this tissue have not been previously investigated by proteomics, in contrast to other studies that focused on LDs in seeds (Jolivet et al, 2004;Liu et al, 2015), seedlings (Pyc et al, 2017b), mesocarp of avocado (Persea americana) (Horn et al, 2013), and chinese tallow (Triadica sebifera; Zhi et al, 2017). In addition, tobacco pollen tubes can be easily transformed to verify the association of candidate proteins with the LDs (Müller et al, 2017), eliminating the need to switch systems from identification to verification.…”
Section: Identification Of Candidate Proteins Associated With Lds Fromentioning
confidence: 99%
“…Therefore, the first goal in this study was to investigate the proteome of LDs to extend the number of known LD-bound proteins. Tobacco pollen tubes were chosen, as LDs of this tissue have not been previously investigated by proteomics, in contrast to other studies that focused on LDs in seeds (Jolivet et al, 2004;Liu et al, 2015), seedlings (Pyc et al, 2017b), mesocarp of avocado (Persea americana) (Horn et al, 2013), and chinese tallow (Triadica sebifera; Zhi et al, 2017). In addition, tobacco pollen tubes can be easily transformed to verify the association of candidate proteins with the LDs (Müller et al, 2017), eliminating the need to switch systems from identification to verification.…”
Section: Identification Of Candidate Proteins Associated With Lds Fromentioning
confidence: 99%
“…Several plant LD proteomics studies have identified VAPs, clathrins, dynamins, and other vesicle-trafficking-related proteins in purified LD fractions (Brocard et al, 2017;Zhi et al, 2017;Kretzschmar et al, 2018). If recruitment of scission-related proteins by AtVAP27-1 to the ER-LD junction is indeed important for formation of LDs in plants, the loss of AtVAP27-1 might result in production of aberrant, large-sized LDs, due to an inability to terminate the process of LD expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Both strategies converged on the vesicleassociated membrane protein (VAMP)-associated proteins (VAPs), particularly the Arabidopsis VAP isoform AtVAP27-1. The presence of VAPs in plant LD proteomes (Brocard et al, 2017;Zhi et al, 2017;Kretzschmar et al, 2018) further attracted our attention. Here, we show that the N termini of both AtSEIPIN2 and AtSEIPIN3 interact specifically and directly with AtVAP27-1 in yeast two-hybrid (Y2H) assays and in plant cells using colocalization and bimolecular fluorescence complementation (BiFC) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining detailed lipidomic profiles from patients at various stages of a disease will be crucial for investigating the aetiology of obesity-related pathologies. Samples rich in lipid droplets are another example [40][41][42].…”
Section: Discussionmentioning
confidence: 99%